2010
DOI: 10.1038/aps.2010.149
|View full text |Cite
|
Sign up to set email alerts
|

Fragile privileges: autoimmunity in brain and eye

Abstract: Brain and eye tissues are subject to a reduced version of immune surveillance, which has evolved to protect the particularly sensitive tissues from accidental bystander damage created by regular inflammatory responses. Yet, there are autoimmune diseases in both organs. This review discusses the nature of immune reactivity in the healthy eye and brain tissues, and mechanisms that can overcome the protective barriers to create tissue specific disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The eye, similar to the brain, possesses a blood-ocular barrier that generally limits immune activation in the ocular tissues [2022]. Whether HIV infection of the eye mirrors that of the brain, with genetically distinct HIV variants that utilize the CCR5 co-receptor and forms a distinct viral compartment from the blood [22], or whether viruses in the eye are in perpetual interchange with variants in the blood, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eye, similar to the brain, possesses a blood-ocular barrier that generally limits immune activation in the ocular tissues [2022]. Whether HIV infection of the eye mirrors that of the brain, with genetically distinct HIV variants that utilize the CCR5 co-receptor and forms a distinct viral compartment from the blood [22], or whether viruses in the eye are in perpetual interchange with variants in the blood, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The uvea within the eye, is an immune privileged site similar to central nervous system and possesses a blood-ocular barrier analogous to brain-blood barrier [2022]. Previous studies have shown that HIV could be recovered from multiple ocular tissues, such as the retina, conjunctiva, cornea, and iris of patients with AIDS [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The retina is a part of the central nervous system and consequently is an immune privileged tissue [ 16 , 59 ]. Ocular immune privilege is physiologically maintained by the blood/retina barrier, but microglia also modulates the process by secretion of pro- or anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is an animal model for multiple sclerosis (MS), where immune cells specific to CNS antigens damage the CNS, resulting in paralysis [64][65][66][67][68][69][70][71][72][73]. Autoimmune T cells traffic to the brain and cross the BBB and causes damage [74], thus preventing T cell migration to the CNS is a therapeutic target.…”
Section: Potential Role Of Cns Lymphatics In Health and Diseasementioning
confidence: 99%